2015
DOI: 10.1021/acs.est.5b01324
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Air Quality and Health Benefits from Avoided Climate Change under Greenhouse Gas Mitigation

Abstract: We evaluate the impact of climate change on U.S. air quality and health in 2050 and 2100 using a global modeling framework and integrated economic, climate, and air pollution projections.Three internally consistent socioeconomic scenarios are used to value health benefits of greenhouse gas mitigation policies specifically derived from slowing climate change. Our projections suggest that climate change, exclusive of changes in air pollutant emissions, can significantly impact ozone (O3) and fine particulate mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 67 publications
8
74
0
1
Order By: Relevance
“…Ensemble-mean projections estimate a climate-induced increase in U.S. annual population-weighted PM 2.5 of 0.5 ± 0.1 μg/m 3 by midcentury and 1.5 ± 0.1 μg/m 3 by the end of the century under the REF scenario (statistical significance evaluated with a Student's t test for 95% confidence). The interactions within these ensemble simulations and impacts on different PM 2.5 components are further discussed in Garcia-Menendez et al (2015). The simulated changes reflect multiple pathways through which meteorology influences PM 2.5 concentrations, including increased SO 2 oxidation and nitrate partitioning to the gas phase under warmer temperatures, higher 10.1029/2019EF001195 stagnation, and variations in precipitation, consistent with previous studies analyzing the linkages between climate and air quality (Fiore et al, 2012).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Ensemble-mean projections estimate a climate-induced increase in U.S. annual population-weighted PM 2.5 of 0.5 ± 0.1 μg/m 3 by midcentury and 1.5 ± 0.1 μg/m 3 by the end of the century under the REF scenario (statistical significance evaluated with a Student's t test for 95% confidence). The interactions within these ensemble simulations and impacts on different PM 2.5 components are further discussed in Garcia-Menendez et al (2015). The simulated changes reflect multiple pathways through which meteorology influences PM 2.5 concentrations, including increased SO 2 oxidation and nitrate partitioning to the gas phase under warmer temperatures, higher 10.1029/2019EF001195 stagnation, and variations in precipitation, consistent with previous studies analyzing the linkages between climate and air quality (Fiore et al, 2012).…”
Section: Resultssupporting
confidence: 81%
“…In CAM-Chem, secondary organic aerosol (SOA) production is represented by a two-product scheme that links SOA formation to oxidation of atmospheric nonmethane hydrocarbons (Lamarque et al, 2012). Additional details and discussion about the CAM-Chem simulations and ensemble-mean PM 2.5 projections used here are included in Garcia-Menendez et al (2015). CAM-Chem has been previously used to model air quality and its ability to replicate surface concentrations of different aerosol species is evaluated against surface observations in Lamarque et al (2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the previous sections, predictions indicate that climate change will worsen O 3 and PM 2.5 pollution across the United States and increase associated health effects (28). Increased temperatures lead to drier conditions, more dust generation, higher risk for wildfires, and increased demand for air conditioning that is largely powered by fossil fuel combustion, all of which contribute to higher PM concentrations (29 (32).…”
Section: Health Implications Of Physical Changes In Earth Climate Sysmentioning
confidence: 95%
“…Many studies have shown that ambient air pollution is related to public health, ecological plant growth, and regional and global climates [1][2][3][4][5][6][7]. A critical component of air pollution is atmospheric PM, which includes fine particles with small diameters that remain suspended in air and do not settle.…”
Section: Introductionmentioning
confidence: 99%